Perkembangan UMKM Di Indonesia Dan Potensi Di Kota Palangka Raya - Muhammad Farras Nasrida; Ausi Pandahang; Dicky Febrian (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2023)
This research examines the role of Micro, Small, and Medium Enterprises (MSMEs) in the national economy and their importance in the context of globalization. The study acknowledges the significant influence of the economic sector as a measure of success for governments in the era of globalization. The dominant presence of MSMEs in the Indonesian economy highlights their strategic role in national development, particularly in economic progress. Despite economic crises, MSMEs have demonstrated resilience and continued growth, proving their ability to withstand challenging circumstances. Additionally, MSMEs have been instrumental in providing employment opportunities and contributing to increased income levels, thus playing a crucial role in reducing unemployment and poverty. The findings emphasize the need for continued government support and strengthening measures to optimize the role of MSMEs as a fundamental pillar in national economic development. This research contributes to understanding the vital contribution and strategic significance of MSMEs in shaping the nation's economy in the context of globalization